PWE-269 A nurse-led colorectal clinic allows streamlining of patient pathways and discharge without consultant input. (22nd June 2015) - Lord, A; Thomas, P; Winter, J; Beck, N
Abstract : Introduction: High numbers of referrals with suspected colorectal cancer have significant resourcing implications. Assessment of all patients in a consultant-led clinic may not be optimising resources. This study aimed to assess the feasibility of nurse led clinic in terms of waiting times, cancer detection rates, missed/delayed diagnoses, and whether benign disease could be managed independently. Method: A database of consecutive patients referred to our fast track nurse led clinic was prospectively maintained. Records of patients referred between September 2012 and January 2014 were obtained and examined retrospectively. Patients were excluded from the clinic if they were aged over 85 or had a palpable mass. Iron deficiency anaemia was also dealt with in a separate clinic so was excluded. A clear algorithm for the management of benign disease was established specifying which patients could be directly discharged, referred to gastroenterology or discharged onto a polyp surveillance programme. Results: 772 patients were included, 46.4% of whom were male. The average age was 67 (range 22–91). Median time from receipt of referral to clinic appointment was 8 days (range 0–36 days). 42 patients (5.4%) waited over 14 days. 675 patients (87%) underwent a colonoscopy, 52 CT colonography, 42 flexible sigmoidoscopy, 33 gastroscopy, and 28 CT. Several patients underwent a combination of investigations. During the study period, 57 cancers were identified (7.4% of referrals). 46 of these were colorectal and 11 were tumours at other sites detected on cross sectional imaging. 168 patients had polyps, 73 had inflammatory bowel disease, 112 had other benign pathology (e.g. haemorrhoids, diverticulosis) and 307 had normal investigations. 507 patients were discharged directly after normal investigation or benign diagnosis. 72 were discharged onto a polyp surveillance programme, 66 patients were referred to gastroenterology with suspected inflammatory bowel disease, 74 patients went on to see a colorectal consultant (47 of whom had cancer) and 18 were referred directly on to another speciality. There was one delayed cancer diagnosis noted. A patient referred to gastroenterology with possible bile salt malabsorption was later sent for a CT which showed a carcinoid tumour of the small bowel. During the study period no other missed cancers or delayed diagnoses were noted. Conclusion: A nurse led clinic for a selected cohort of patients is feasible with similar cancer detection rates as a consultant led clinic. Most patients were seen within 2 weeks. There was only one delayed diagnosis. Most patients with benign pathology could be discharged or referred on without consultant input. Consultant time can be optimised by only seeing patients once cancer is confirmed or where more complex management decisions are needed. Disclosure of interest: None Declared.